ANALYSIS OF THE NORMATIVE LAW ENFORCEMENT OF THECRIME OF INSULTING THE STATE SYMBOL:CASE STUDY OF THE INSULT TO THE STATE COAT OF ARMS BYZASKIA GOTIK AND HABIB RIZIEQ - Hermanto, Budi (International Review of Humanities Studies, 2021)
Cases of insulting the national emblem are increasing and attracting attention. A number of cases of allegations of insulting the national emblem have brought up a number of names, from celebrities, religious and community leaders, teenagers and students, to organizations. Two cases that were busy were allegations of insulting the national emblem by Zaskia Gotik and Habib Rizieq, which appeared at a similar period. Various studies regarding the alleged humiliation of the state symbol by Zaskia Gotik and Habib Rizieq have been widely studied. However, most of the studies focused on linguistic and communication perspectives. Unlike previous studies, this paper intends to examine the aspects of criminal law enforcement in both cases. To answer the research problems raised, the author uses important concepts in punishment and also the theory of legal certainty. This study is a normative juridical study with secondary data as material for analysis. This research reveals that law enforcement in cases of alleged insulting the state symbol by Zaskia Gotik and Habib Rizieq provides legal certainty because of the existence of corridors or guidelines in declaring the act guilty or not legally. The corridor refers to Law no. 24 of 2009 which regulates the symbols of the state, one of which is the symbol of the state, both regarding the meaning, prohibition, and threat.